What can be learned from real-world data about chronic spontaneous urticaria? - Bakay, Ozge Sevil Karstarli; Kacar, Nida; Gul, Burak; Goksin, Sule; Gural, Yunus (Ocean Side Publications Inc, 2024)
Background: Chronic spontaneous urticaria (CSU) is a common disease with complex pathogenesis. Patients' clinical characteristics and responses to treatment vary. Objective: We aimed to investigate the role of data obtained from routinely recommended tests in predicting the response to omalizumab, the only biologic agent approved for treatment, and in defining fi ning the clinical characteristics of the patients. Methods: A retrospective study of patients who started omalizumab treatment for CSU between 2015 and 2022 at the Department of Dermatology, Pamukkale University, was conducted. Response criteria were based on the urticaria control test, and patients with a urticaria control test score <12 at 6 months were considered treatment non-responders. Eosinophil and basophil counts, neutrophil-lymphocyte ratio (NLR), systemic immune inflammation fl ammation index (SII), systemic inflammation fl ammation response index (SIRI), and total immunoglobulin E (IgE) levels of the patients were evaluated before treatment and at the sixth month of treatment. Results: A total of 23.1% of the patients were unresponsive to omalizumab. The response rate to the omalizumab treatment of the patients with a total IgE level 30 IU/L (n = 4 [5.7%]) was significantly fi cantly lower than patients with total IgE level > 30 IU/L (n = 66 [94.3%]) (p = 0.015). The mean +/- standard deviation SIRI levels were significantly fi cantly higher in non-responders versus responders (1.53 +/- 1.03 versus 1.15 +/- 7.76; p = 0.026). Eosinophil counts positively correlated with basophil counts (r = 587; p < 0.001) and IgE levels (r = 0.290; p = 0.005) but a negative correlation was found with levels of NLR (r = 0.475; p < 0.001), SIRI (r = 0.259; p = 0.013), and SII (r = 0.285; p = 0.006). NLR levels were lower in CSU patients with atopy, than in those without atopy (1.9 +/- 0.9 vs 2.9 +/- 2.1, p = 0.022). Conclusion: We suggest that eosinopenia and high NLR levels are linked to autoimmune CSU. Predicting a poor response to omalizumab seems possible with total IgE levels < 30 IU/L and high SIRI levels.
Keywords: Omalizumab Treatment; Ige; Eosinophils; Parameters; Ratio